Fabrikasi Elektroda Pembanding Ag/AgCl dengan Berbagai Membran - Fredy Kurniawan (Akta Kimia Indonesia, 2017)
Ag/AgCl reference electrode has been fabricated using various types of membranes, i.e. cellulose, polyisoprene, graphite, kaolinite, and LDPE. The electrodes performance were observed by measuring 0.1 M K4[Fe(CN)6] solution.  The measurements were repeated for every 2 hours during  24 hours, then every 24 hours during  6 days, and after that every 3 days for two times using cyclic voltammetry. The voltammograms obtained of various membranes were compared to Ag/AgCl commercial reference electrode voltammogram. Validation of the results was conducted by F-test and t-test. The Ag/AgCl reference electrode using polyisoprene and LDPE membranes have a performance close to commercial electrode.